The Impact of Self Assesment System Implementation and Tax Collection on Value Added Tax Revenue at KPP Madya Bandung - Arianti, Fira; Masruri, Fahrul Alam; Rahman, Erpi (LPPM Universitas Sebelas April, 2024)
This research is motivated by the lack of awareness of taxpayers in paying value added tax based on the number of VAT periods and uncollectible tax arrears for value added tax for 2019- 2023. This research aims to find out how much influence the self assessment system and Tax Collection have on Value Added Tax Revenue. The research methods used in this research are quantitative methods and survey methods. Data collection was used using a random sampling technique by distributing questionnaires to 98 respondents as samples. The data analysis techniques used in this research are normality test, multiple linear regression analysis, Pearson correlation analysis, coefficient of determination (R²) analysis, t-test and f-test hypothesis testing using the IBM SPSS Version 25 program. The results of this study show that : (1) The Self Assessment System has a positive and significant effect on Value Added Tax Revenue, with a regression coefficient of 0.349, a Determination Coefficient (R²) value of 0.201 or 20.1%, the effect is low but certain, and the rest is influenced by other variables that are not researchers discussed in this research, the t-count value > t- table (3.800>1.6608) with a significant value of 0.001<0.05. (2) Tax collection has a positive and significant effect on Value Added Tax Revenue, with a regression coefficient of 0.165, a Determination Coefficient (R²) value of 0.152 or 15.2%, the influence is low, and the remainder is influenced by other variables that the researchers did not discuss in the research In this case, the t-count>t- table value is (2.914>1.66088) with a significant value of 0.004<0.05. (3) The Self Assessment System and Tax Collection have a positive and significant effect on Value Added Tax Revenue. With a Coefficient of Determination (R²) value of 0.267 or 26.7%, the influence is sufficient, and the rest is influenced by other variables that the researchers did not discuss in this study. And with a value of F- count>F-table (17.265>3.09) with a significant value of 0.001<0.05